2017
DOI: 10.1016/j.poly.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Chelating properties of EDTA-type ligands containing six-membered backbone ring toward copper ion: Structure, EPR and TD-DFT evaluation

Abstract: The P-APC ligands (EDTA-like aminopolycarboxylate ligands comprising 1,3-propanediamine backbone) H 4 pdta, H 4 pd3ap, H 4 pddadp and H 4 pdtp (H 4 pdta = 1,3-propanediamine-N,N,N 0 ,N 0 -tetraacetatic acid; H 4 pd3ap = 1,3-propanediamine-N,N,N 0 -triacetic-N 0 -3-propionic acid; H 4 pddadp = 1,3-propanediamine-N,N 0 -diacetatic-N,N 0 -di-3-propionic acid; H 4 pdtp = 1,3-propanediaminetetra-3-propionic acid) were investigated. The chelating ligands coordinate to copper(II) via five or six donor atoms affording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…S4. The coordination compound itself is sufficiently flexible, as shown earlier, [34] and this allows to fit in the available channel intersection. The calculated binding energy with respect to isolated Na 2 [Cu-EDTA] coordination compound and empty zeolite model is large (-317 kJ/mol).…”
Section: Effect Of Calcination and Presence Of Sodium Cations On The ...mentioning
confidence: 95%
“…S4. The coordination compound itself is sufficiently flexible, as shown earlier, [34] and this allows to fit in the available channel intersection. The calculated binding energy with respect to isolated Na 2 [Cu-EDTA] coordination compound and empty zeolite model is large (-317 kJ/mol).…”
Section: Effect Of Calcination and Presence Of Sodium Cations On The ...mentioning
confidence: 95%
“…The vibration at 1626 cm −1 which is assigned to antisymmetrical carboxyl stretching of CrPDTA, [45][46][47][48] is redshifted by 11 cm −1 with increasing urea concentration, strongly indicating that CrPDTA H-bonds with urea (Figure 3c). Similar carboxyl-urea interactions have previously been studied in the area of supramolecular chemistry and have been exploited for neutral anion receptors.…”
Section: Disturbed Urea Agglomeration and Anion Recognitionmentioning
confidence: 98%
“…A smaller 13 C NMR upshift with KCrPDTA is observed and KCrPDTA concentration dependent IR redshifts of ca. 2 cm −1 for the vibration at 1361 cm −1 , assigned to symmetrical carboxyl stretching modes of the CrPDTA anion, [45][46][47][48] indicate weaker CO bonds, i.e., interaction of anion carboxyl groups with a positive charge (Figure S4c). For the same vibration, a urea concentration dependent redshift of comparable 2 cm −1 is observed at a constant salt concentration of 500 mм KCrPDTA (Figure S4d).…”
Section: Disturbed Urea Agglomeration and Anion Recognitionmentioning
confidence: 99%
“…Numerous studies have demonstrated that Cu mobility is mainly controlled by sorption to soil organic matter (SOM), where carboxylic and hydroxylic (or amine) groups form very stable five-to sixmembered ring chelates with Cu 2+ [11,18,21,27,35]. Cu can also adsorb to Fe-, Mn-or Al-(hydro)oxides, and clay minerals, forming inner-sphere complexes and/or surface precipitates [7,8,14,46].…”
Section: Introductionmentioning
confidence: 99%